How do Students Perceive Guided Writing in Learning Descriptive Text? - Fardatun Isnaeni; Mega Mulianing Maharani; Elok Widiyati; Nur Ekaningsih (Universitas Islam Sultan Agung, 2022)
The purpose of this study was to investigate how students perceive about guided writing as a means of learning descriptive text. Descriptive quantitative method was employed, and a questionnaire served as the data collection tool. Seventy ninth graders from one school in Central Java made up the study's sample. The questionnaire has 16 questions broken down into 4 categories: the effectiveness of the timing, the easiness of using correct spelling, the support from the teacher, the benefits of guided writing. The data analysis showed that students had a favorable impression of guided writing. It also demonstrated the usefulness of guided writing as a teaching method for writing a descriptive text.